2005
DOI: 10.1111/j.1464-410x.2005.05728.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is associated with subnormal serum levels of free testosterone in men

Abstract: analysis correlating DM and elevated BMI ( > 25 kg/m 2 ) and WHR ( > 1) with the presence of subnormal FT and TT levels was performed. RESULTSFT and TT serum levels were subnormal in 46% and 34% of diabetics, respectively, and in 24% and 23% of nondiabetics. Subnormal FT levels were strongly correlated with DM (odds ratio (OR) 2.7; 95% confidence interval (CI) 1.8-4.1) but not with elevated BMI (OR 1.4; 95% CI 1.0-2.0). Subnormal TT levels were more strongly associated with elevated BMI and WHR (OR 2.6; 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 32 publications
6
53
1
4
Order By: Relevance
“…This observation has been confirmed by several previous studies (6,16,17,18,19). Low testosterone levels are common in patients with T2DM.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This observation has been confirmed by several previous studies (6,16,17,18,19). Low testosterone levels are common in patients with T2DM.…”
Section: Resultssupporting
confidence: 79%
“…Cross-sectional epidemiological studies have reported a direct correlation between plasma testosterone and insulin sensitivity (2), and low testosterone levels have been associated with an increased risk of T2DM, which has been illustrated by androgen deprivation in men with prostate carcinoma (3). Several studies have suggested that men with low testosterone are at a greater risk of developing T2DM and may even predict the onset of diabetes (4)(5)(6)(7)(8). A systematic review of 43 studies including 6427 men by Ding, et al suggested that higher plasma levels of testosterone were associated with lower risk of T2DM and vice versa (9).…”
Section: Introductionmentioning
confidence: 99%
“…Rhoden et al [22] also demonstrated that subnormal free testosterone concentration had a stronger correlation with the presence of diabetes mellitus than subnormal total testosterone concentration.…”
Section: Discussionmentioning
confidence: 94%
“…8 A Australia study reported that MHG prevalence 43% of type 2 diabetes patients with TT levels <288 ng/dl, while in the United Kingdom, MHG prevalence 17% with TT<231 ng/dl and 34% in Brazilian study by using free testosterone. [9][10][11] In Arabic world, MHG defined as TT less than 300 ng/dl was estimated to be 36.5% in patient with type 2 DM. 8 A recent study from Egypt reported 33.2% HG in type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%